2006
DOI: 10.1103/physrevlett.96.023003
|View full text |Cite
|
Sign up to set email alerts
|

Self-Sustained Oscillations in a Large Magneto-Optical Trap

Abstract: We have observed self-sustained radial oscillations in a large magneto-optical trap (MOT), containing up to 10 10 Rb 85 atoms. This instability is due to the competition between the confining force of the MOT and the repulsive interaction associated with multiple scattering of light inside the cold atomic cloud. A simple analytical model allows us to formulate a criterion for the instability threshold, in fair agreement with our observations. This criterion shows that large numbers of trapped atoms N > 10 9 ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
91
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(101 citation statements)
references
References 21 publications
10
91
0
Order By: Relevance
“…Above that limit, self-sustained mechanical instabilities take place [13], so we should avoid this situation in the present work.…”
mentioning
confidence: 99%
“…Above that limit, self-sustained mechanical instabilities take place [13], so we should avoid this situation in the present work.…”
mentioning
confidence: 99%
“…Recently, Wilkowski et al found the instability phenomena in a MOT and explained them by means of shadow effect (Wilkowski et al, 2000;di Stefano et al, 2003). In addition, MOT exhibits very unique collective effects and critical behaviors when the number of atoms increases such as instability-induced pulsation (Labeyrie et al, 2006), and plasma oscillations of ultracold neutral plasma (Kulin et al, 2000). In this article we present experimental and theoretical works on the applications of the magneto-optical trap by modifying the trap conditions, which is termed as an asymmetric magneto-optical trap (AMOT).…”
Section: Introductionmentioning
confidence: 99%
“…These features are also used to describe the so-called active Brownian particles in the context of plasma physics [10] or biological physics [11][12][13]. In cold atoms experiments, a space dependent friction may have important dynamical consequences for the stability of magneto-optical traps [14,15]. Finally, let us also mention that trapping anharmonicity may be essential to understand the dynamics of BoseEinstein condensate [16].…”
Section: Introductionmentioning
confidence: 99%